ELECTROPHYSIOLOGICAL EFFECTS OF VALSALVA MANOEUVER DURING EARLY PREGNANCY IN PATIENTS WITH PAROXYSMS OF ORTHODROMIC ATRIOVENTRICULAR TACHYCARDIA - Rakhmatullov, Fagim Kasymovich; Kuryaeva, Alsu Muzafyarovna; Moiseeva, Inessa Jakovlevna; Burmistrova, Larisa Fedorovna; Dyatlov, Nikita Evgen’evich (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim is to study electrophysiological (EPh) indicators of the heart in pregnant women in the first trimester with orthodrome paroxysms of reciprocal atrioventricular tachycardia during the Valsalva test, after a single dose of propafenone and a combination of Valsalva test with propafenone. Methods: Clinical survey, assessment of medical history, physical examination, electrocardiogram (ECG) in 12 leads, Holter ECG monitoring, echocardiography, expert ultrasound examination of the fetus, transesophageal EPh study of the heart, the blood test for electrolytes (potassium, sodium), thyroid hormones (T3, T4, thyroid-stimulating hormone) were included in this study. We examined 28 women during an early gestation. Results: We found that the Valsalva manoeuver, Propanorm, and the combination of the Valsalva manoeuver and Propanorm produced an antiarrhythmic effect through the anterograde and retrograde conduction in reentry. Discussion: The study is the first to reveal that the Valsalva manoeuver influences retrograde conduction in reentry in pregnant patients. Conclusion: We proved that it is necessary to use the Valsalva manoeuver to stop paroxysms of orthodromic atrioventricular tachycardia (POAVRT) in the first trimester of pregnancy. If the manoeuver is ineffective, it is advisable to use Propanorm or combination of Propanorm with Valsalva manoeuver.